Identifying optimal solutions between competing economic and conservation land use objectives for species that require widely distributed resources. (February 2022) - Mastrantonis, Stanley; Craig, Michael D.; Hobbs, Richard J.; Grigg, Andrew H.; Renton, Michael
Abstract: Across the world, wildlife must coexist with humans in modified and increasingly fragmented landscapes but balancing the competing land use objectives of economic production and conservation is challenging. Multi-objective optimisation and spatial conservation prioritisation can inform land use planning but have not yet explicitly accounted for the way species access multiple resources at different locations in a landscape. Here, we demonstrate a novel approach for conservation prioritisation that accounts for the spatial distribution of different resources as well as a species' movements. This suite of tools and models identifies Pareto-optimal solutions to competing objectives of economic production on the one hand, with conserving a species' food, drink and shelter requirements and movement corridors on the other. We demonstrate the broader functionality of these tools using a case study with competing objectives of clearing land for mining versus conservation of a vulnerable endemic species . Highlights: This paper presents a novel decision-tool framework for spatial conservation prioritisation and land use optimisation. Here, we demonstrate these tools on simulated and generalized datasets to showcase their functionality. These tools incorporate Pareto efficiency principles to optimise economic and conservation objectives. We include a heuristic algorithm that will identify optimal locations for compensatory conservation actions.